Analyses of national mountain lion harvest indices yield ambiguous interpretations. Issue 2 (6th June 2022) - Elbroch, L. Mark; Petracca, Lisanne S.; O'Malley, Connor; Robinson, Hugh
Abstract: Wildlife managers make difficult decisions about how best to ensure sustainable wildlife populations. This is especially contentious in the absence of accurate abundance data. Currently, many managers rely upon harvest metrics to monitor mountain lion abundance and to set management objectives. We analysed mountain lion harvest data from 2005 to 2016 across 10 U.S. states to determine mountain lion metapopulation trends. Our results were ambiguous and suggested conflicting population trends. Three hunting metrics indicated that the metapopulation was declining, two metrics could be interpreted as support for either an increasing or decreasing metapopulation and one metric indicated that the mountain lion metapopulation was stable. This ambiguity may indicate that some metrics better reflect carnivore abundance than others or that harvest metrics are a poor method for monitoring carnivore abundance. This is a concern because ambiguity in population trends may also fuel conflict between different stakeholder groups with different views of mountain lions. To avoid future ambiguity and to mitigate dissension among stakeholders, state agencies might consider a collaborative integrated population model to monitor mountain lions at a national scale. Abstract : We analysed national mountain lion harvest indices to assess metapopulation trends. The results were ambiguous, and different indices suggested different trends. This ambiguity may fuel stakeholder conflict among those with different perspectives on mountain lions.